Efficacy of potential biocontrol agents for control of Fusarium verticillioides and fumonisin B1 under different environmental conditions - Samsudin, Nik Iskandar Putra; Magan, Naresh (Wageningen Academic Publishers, 2016)
A mycotoxigenic strain of Fusarium verticillioides previously isolated from Malaysian maize kernels and identified morphologically and molecularly was used in the present work. The objectives were (1) to screen the competitiveness of three potential antagonists isolated from Malaysian maize and three other known candidates for control of growth of F. verticillioides in vitro based on interaction scores, growth rates and hyphal area of F. verticillioides, and (2) to examine the best candidates using different spore/cell ratios on milled maize agar at different water activity conditions on relative control of fumonisin B1 (FB1). Three fungi and three bacteria (BCAs 1-6) were examined for antagonistic effects against F. verticillioides in dual-culture assays. These showed that all fungal candidates intermingled with F. verticillioides while all bacterial candidates inhibited F. verticillioides on contact or at a distance, which in turn decreased the growth rates and hyphal area of F. verticillioides significantly. Although BCA1 (Clonostachys rosea 016) did not inhibit growth or hyphal area of F. verticillioides, it was included in FB1 inhibition studies with other bacterial candidates (BCA4, Streptomyces sp. AS1; BCA5, Gram-negative rod; BCA6, Enterobacter hormaechei) because of its established mycoparasitism. The FB1 inhibition studies were conducted on milled maize agar with different spore/cell ratios of pathogen:antagonist mixtures at 0.95/0.98 water activity (aw) and 25 °C for 14 days. FB1 biosynthesis for all treatments was significantly higher at 0.95 than 0.98 aw. Of the four antagonists tested, the best was BCA1 which inhibited FB1 biosynthesis by 73 and 100% at 0.95 and 0.98 aw, respectively. BCA5 was the next best, resulting in 38 and 78% FB1 inhibition at 0.95 and 0.98 aw, respectively. The pathogen:antagonist ratios for BCA1 and BCA5 showed best results at 50:50 and 25:75. These results were discussed in context of using biocontrol agents to minimise fumonisins in maize.